The influence of human resource information systems on employee performance within the Ministry of Communications and Transportation in the Kingdom of Bahrain - Ateeq, Ali; Alfiras, Mohanad; Alaghbari, Mohammed Abdulrazzaq; Almuraqab, Nasser A. Saif (Frontiers in Communication, 2025)
BackgroundEmployee performance (EP) is a key factor in organizational success. Nonetheless, the impact of particular factors on EP remains variable across research. This study investigated the influence of Communication and Collaboration (CC), Employee Efficiency (EE), Level of HRIS Training (LHT), and Performance Analysis (PA) on Employee Performance (EP) within the Ministry of Communications and Transport (MCCT) in Bahrain.MethodsA quantitative, descriptive-correlational methodology was employed. Data were obtained from 243 convenience-sampled participants, with 167 valid responses subjected to analysis. Reliability was established through Cronbach’s alpha (α = 0.827). Descriptive statistics were conducted using SPSS v28, and Partial Least Squares Structural Equation Modeling (PLS-SEM) was executed with SmartPLS 4. The model’s validity was assessed through reliability indices, AVE, VIF, and goodness-of-fit indices.ResultsThe analysis indicated that CC (β = 0.268, p = 0.002), EE (β = 0.280, p = 0.012), and LHT (β = 0.261, p = 0.006) exerted significant positive influences on EP. Conversely, PA (β = 0.067, p = 0.272) exhibited no statistical significance. Effect size analysis (f2) revealed minimal contributions (0.029–0.094), although CC and EE revealed a comparatively greater impact. The model accounted for R2 = 0.335 (33.5%) of the variance in EP, indicating moderate explanatory efficacy. The fit indices satisfied the prescribed thresholds (e.g., CFI = 0.982, TLI = 0.977, RMSEA = 0.072).ConclusionThe study concludes that CC, EE, and LHT are substantial determinants of PE, whereas AP shown no direct effect. The findings underscore the significance of communication, efficiency, and training in enhancing employee outcomes, while also indicating the need for further research on the contextual role of performance analysis.